1996
DOI: 10.1002/j.2161-007x.1996.tb00843.x
|View full text |Cite
|
Sign up to set email alerts
|

Employing Ethical Codes and Decision‐Making Models: A Developmental Process

Abstract: Counselors often encounter seemingly intractable ethical dilemmas. To assist counselors who face difficult situations, the helping professions have generated both ethical codes and decision‐making models. Because the process of decision making seems to be related to cognitive‐moral development, this article details ethical codes and decision models and speculates on how counselor level of development may influence use of such codes and models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Addressing the argument that it could be assumed that graduate students had already gained the necessary conceptual skills for identifying and analyzing moral issues as undergraduate students, Losito noted that most undergraduates took only one course in philosophy and that this single course was insufficient to presume the development of such sophisticated skills. Like many others (e.g., Engels, 1981;Kitchener, 1984b;Mabe & Rollin, 1986;Neukrug, Lovell, & Parker, 1996;Talbutt, 1981), Losito recognized the limitations of codes of ethics. He indicated that the argument that it was enough for professionals to know their code(s) of ethics was erroneous.…”
Section: Early Calls For Attention To Philosophymentioning
confidence: 96%
“…Addressing the argument that it could be assumed that graduate students had already gained the necessary conceptual skills for identifying and analyzing moral issues as undergraduate students, Losito noted that most undergraduates took only one course in philosophy and that this single course was insufficient to presume the development of such sophisticated skills. Like many others (e.g., Engels, 1981;Kitchener, 1984b;Mabe & Rollin, 1986;Neukrug, Lovell, & Parker, 1996;Talbutt, 1981), Losito recognized the limitations of codes of ethics. He indicated that the argument that it was enough for professionals to know their code(s) of ethics was erroneous.…”
Section: Early Calls For Attention To Philosophymentioning
confidence: 96%
“…Garfat & Ricks, 1995;Hill, Glaser, & Harden, 1995;Neukrug, Lovell, & Parker, 1996;Pettifor, 1996;Plante, 1995;Woody, 1990). The problem is that individuals cannot read ethical dilemmas "objectively."…”
mentioning
confidence: 98%
“…Additionally, lapses in ethical judgment from prestigious, credible, and powerful corporate employees can undermine the credibility of their organizations or professions (Bayles, 1981; Frankel, 1989; Savan, 1989; Kerr & Smith, 1995). Indeed, ethical codes of conduct provide a valuable source of information for individuals engaged in ethical decision making (Neukrug, Lovell, & Parker, 1996). A code of ethics is a written, formal document consisting of moral standards and guidelines intended to help guide employee or corporate behavior (Schwartz, 2002; Stevens, 1994).…”
mentioning
confidence: 99%